Data on Medicare eligibility and cancer screening utilization - Meyer, Christian P. (Data Brief, 2016)
Health insurance is associated with increased utilization of cancer screening services. Data on breast, prostate and colorectal cancer screening were abstracted from the 2012 Behavioral Risk Factor and Surveillance System. This data in brief includes two sets of analyses: (i) the use of cancer screening in individuals within the low-income bracket and (ii) determinants for each of the three approaches to colorectal cancer screening (fecal occult blood test, colonoscopy and sigmoidoscopy+fecal occult blood test). Covariates included education attainment, residency, and access to health care provider. The data supplement our original research article on the effect of Medicare eligibility on cancer screening utilization “The impact of Medicare eligibility on cancer screening behaviors” [1].